Dependence of Propagation Rate Coefficients in Radical Polymerization on Solution Properties: A Quantitative Thermodynamic Interpretation. Issue 4 (17th May 2018) - Deglmann, Peter; Hungenberg, Klaus‐Dieter; Vale, Hugo M.
Abstract: The thermodynamic formulation of the transition state theory is applied to quantitatively explain the effect of the medium (solvent type and concentration) on the propagation rate coefficient k p in radical polymerization. The magnitude of the medium effect is shown to be linked to the degree of thermodynamic nonideality of the system and, more specifically, to the value of the activity coefficients of the species involved in the transition state quasi‐equilibrium (monomer, propagating radical, and propagation transition state). To illustrate and validate this approach, the quantum chemistry–based method COSMO‐RS (Conductor‐like Screening MOdel for Real Solvents) is used to estimate the relevant activity coefficients for a wide variety of monomer–solvent combinations for which k p measurements are published. Overall, satisfactory agreement between observed and predicted k p variations is found. It is also shown that the medium effect may be split into a sum of combinatorial and residual contributions, which provides further insight into the origin of k p variations. Last but not least, for particular cases, simplified methods are proposed to estimate the magnitude of the medium influence upon k p without the need to carry out quantum‐chemical calculations. Abstract : Transition state theory is applied to quantitatively explain the medium effect on k P in radical polymerization for a wide range of monomers, solvents, and concentrations. The quantum chemistry–based method COSMO‐RS is used to estimate the relevant activity coefficients of the species involved in the transition state quasi‐equilibrium.